2005
DOI: 10.1152/japplphysiol.00753.2004
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and acid-base changes in men during prolonged exercise with and without sodium-lactate infusion

Abstract: An emerging technique used for the study of metabolic regulation is the elevation of lactate concentration with a sodium-lactate infusion, the lactate clamp (LC). However, hematological and acid-base properties affected by the infusion of hypertonic solutions containing the osmotically active strong ions sodium (Na(+)) and lactate (Lac(-)) are a concern for clinical and research applications of LC. In the present study, we characterized the hematological and plasma acid-base changes during rest and prolonged, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 44 publications
(78 reference statements)
3
35
0
Order By: Relevance
“…The infusion of sodium lactate presents a special case of inducing a MALK for at least two reasons: (1) lactate − is a strong acid anion and (2) there is a suppression of VE (205,206,301) that seemingly occurs independent of the decrease in arterial plasma [H + ] (301) and in the absence of change in PCO 2 both at rest and during moderate-intensity exercise (206). While lactate − is a strong acid anion in physiological solution because of its pK , it is somewhat unique, compared to strong inorganic anions such as Cl − , because of its ability to rapidly enter cells and be oxidized (204 Figure 21 Scheme of interactive processes operating during an induced respiratory alkalosis.…”
Section: Experimentally Induced Metabolic Alkalosismentioning
confidence: 99%
“…The infusion of sodium lactate presents a special case of inducing a MALK for at least two reasons: (1) lactate − is a strong acid anion and (2) there is a suppression of VE (205,206,301) that seemingly occurs independent of the decrease in arterial plasma [H + ] (301) and in the absence of change in PCO 2 both at rest and during moderate-intensity exercise (206). While lactate − is a strong acid anion in physiological solution because of its pK , it is somewhat unique, compared to strong inorganic anions such as Cl − , because of its ability to rapidly enter cells and be oxidized (204 Figure 21 Scheme of interactive processes operating during an induced respiratory alkalosis.…”
Section: Experimentally Induced Metabolic Alkalosismentioning
confidence: 99%
“…Miller et al (2005) have reported that the LC method allows an increase in lactate without causing acidosis; in fact, LC caused a mild alkalosis. LC did not increase ventilation or rating of perceived exertion, suggesting that the LC can be used to solely study the effect of lactate, rather than acidosis, on metabolic functions.…”
Section: Future Researchmentioning
confidence: 99%
“…The preference of working muscle for lactate over glucose has been established in combined lactate clamp and tracer studies [36], [37], [38]. The apparent preference for fructose over glucose is likely attributable to the conversion of fructose to lactate and subsequent use of lactate derived from exogenously supplied fructose ( vide supra ).…”
Section: Discussionmentioning
confidence: 98%